Cord blood Per- and polyfluoroalkyl substances, placental steroidogenic enzyme, and cord blood reproductive hormone. (August 2019) - Yao, Qian; Shi, Rong; Wang, Caifeng; Han, Wenchao; Gao, Yu; Zhang, Yan; Zhou, Yijun; Ding, Guodong; Tian, Ying
Abstract: Background: Per - and polyfluoroalkyl substances (PFASs) are widely used in China, but little is known about the association between prenatal PFASs exposure and fetal reproductive development as well as its potential mechanism. Objective: We investigated the effects of cord blood PFASs on fetal reproductive hormones and its potential mechanism in relation to steroidogenic enzymes. Methods: Ten selected PFASs ( n = 351) including PFOS, PFOA, PFBS, PFDA, PFDoA, PFHpA, PFHxS, PFNA, PFOSA, and PFUA, and two reproductive hormones estradiol (E2) (n = 351) and testosterone (T) ( n = 349) were measured in 351 cord blood serum samples from a Chinese birth cohort between 2010 and 2013. Three steroidogenic enzymes including P450arom ( n = 125), 3β-HSD1 ( n = 123), and 17β-HSD1 ( n = 116) were measured in 125 placental tissue samples. Linear regression tested the associations between cord blood PFASs and reproductive hormones in cord blood. Mediation analysis assessed the role of placental steroidogenic enzymes between cord blood PFASs and reproductive hormones. Results: The positive associations between PFOA, PFHxS and E2 levels, PFOS, PFUA, PFNA and T levels, and PFOS, PFUA and T/E2 ratio were significant. PFUA, PFNA, PFDA, PFHxS, and ∑PFASs were associated with higher P450arom levels. PFHxS was also associated with increased 3β-HSD1 and 17β-HSD1 levels. These associations were more pronounced in females than males when stratified by gender. Furthermore, 17β-HSD1 demonstrated mediating effects in the positive association between cord blood PFHxS and E2 levels in females. Conclusion: Our findings suggested the potential impacts of cord blood PFASs on fetal reproductive hormones, in which steroidogenic enzymes may play important roles. These associations were more pronounced in females than males. Highlights: Per - and polyfluoroalkyl Substances (PFASs) are widely used in China. We examined the link of PFASs with reproductive hormones and potential mechanisms. PFASs were positively associated with E2, T, and T/E2 ratio. PFASs were positively associated with P450arom, 3β-HSD1, and 17β-HSD1. PFHxS induced 17β-HSD1 that may lead to increased E2 particularly in females.